IDENTIFIKASI TITIK KEMACETAN DAN ALTERNATIF PENANGANANNYA DI KECAMATAN PONTIANAK TIMUR, PONTIANAK SELATAN, PONTIANAK TENGGARA - FENDI, GUSTAF SAPTO; SULANDARI, ETI; ., SAID (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2014)
Growth and development of the city have an impact on the problem of traffic systems. The impact associated with the influence of road capacity and traffic volume, which can cause traffic congestion problem. From 3 districts who studied the East Pontianak, Pontianak South, Southeast Pontianak there are 9 point jam, and 2 of them experienced severe congestion that is the intersection of Jalan Sultan Hamid II - Jalan Imam snag - Way Hero - Road Tanjungpura and U-Turn at the next gas station OSO segment Ahmad Yani street. The purpose of this paper is to identify the point - the point of congestion and causes congestion in the districts East Pontianak, Pontianak South, and Southeast Pontianak so may submit management plans and programs of action plans that can be done to address the problem of traffic congestion in the district of East Pontianak, South Pontianak, Pontianak and Southeast for now.  In this study, the data obtained by several agencies that BPS and POLRESTA city of Pontianak. The survey has been carried out, namely traffic volume survey conducted on Sunday (17 November 2013), on Monday (18 November 2013), in the morning at 6:00 a.m. to 9:00, lunch at 11:00 to 14:00, afternoon at 4:00 p.m. to 18:00 pm. The geometric survey conducted on Sunday (24 November 2013) .From these survey results taken 2 points were considered to be the most severe congestion that will be calculated and analyzed so that it will acquire the capacity and degree of saturation. The degree of saturation can be used as an indicator of the level of performance of an intersection and road segment. Where the degree of saturation can directly determine the performance of a road. Based on Indonesian Highway Capacity Manual for urban roads in 1997, requires the degree of saturation does not exceed 0.85. Based on the results obtained in 2013 the degree of saturation at Jalan Sultan Hamid II is 0.87, Jalan Imam Bonjol of 0.95, 0.70 at Jalan Pahlawan, Jalan Tanjungpura of 0.89 and a U-Turn at the next gas station OSO road Ahmad Yani direction Roundabout to Untan ie 0:56, 0:57 direction to the PCC that although the degree of saturation of <0.85 but the area can be said to be congested due to the long queue of vehicles that will pass through the U-Turn, disrupt traffic flow on the road Ahmad Yani. This indicates that in 2013 the 2 point of congestion experienced traffic problems. For those reasons, given the alternative solution is to operationalize back Public Transport Buses in particular, so as to reduce the degree of saturation in the region studied.